Síntese de 2-fenil-3H-pirimidin-4-onas 6-metilsubstituídas e 4- trifluormetil-2-ureído pirimidinas - Fantinel, Leonardo (2009)
This study was carried out in three parts: At first, three methods for the bromination of 6-alkylsubstituted 2-phenyl-3H-pyrimidin-4-ones was developed for the synthesis of: (i) a new series of 6-alkylsubstituted 5-bromo-2-phenyl-3H-pyrimidin-4-ones, (ii) a new series of 6-(1-bromoalkyl)-2-phenyl-3H-pyrimidin-4-ones, and (iii) e new series of 5-bromo-6-(1-bromoalkyl)-2-phenyl-3H-pyrimidin-4-ones. On the second part, the brominated pyrimidines obtained, were used to synthesize new 6-methylsubstituted 2-phenyl-3Hpyrimidin-4-ones from the reaction of the brominated pyrimidinones with primary and secondary amines, pyridine and sodium azide. On the third part, a new series of 5- e 6-substituted 4-trifluoromethyl-2-ureido pyrimidines was prepared, in good yields, from the cyclocondensation reaction of β- alkoxyvinyl-trifluoromethylketones substituted and dicyanodiamide. The products synthesized in this study were obtained in good yields and were characterized by GC-MS and 1H e 13C RMN spectroscopy. The purity of the products was assured by elemental analysis. Some compounds such as 5-bromo-2-phenyl-6-propyl-3H-pyrimidin-4-one, 5-bromo-6-(1- bromopropyl)-2-phenyl-3H-pyrimidin-4-one, 5-bromo-6-(1-bromobutyl)-2-phenyl-3H-pyrimidin-4-one, 6-(1-azidoethyl)-5-bromo-2-phenyl-3H-pyrimidin-4-one, 6-(1-azidopropyl)-5-bromo-2-phenyl-3H-pyrimidin-4-one, and 6-(1-azidobutyl)-5-bromo-2-phenyl-3H-pyrimidin-4-one, exhibited significant antimicrobial activity against some microorganisms, such as Candida albicans, Saccharomyces cerevisiae, Staphylococcus aureus, Salmonela, Klebsiela pneumonie among others.